2017
DOI: 10.19080/gjo.2017.04.555647
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of 1.5 Mm Low Profile Titanium Miniplate As a Tension Band in Treatment of Mandibular Parasymphyseal Fractures

Abstract: Patients and MethodsI.Patient Selection a) Inclusion criteria: patients included suffered from trauma to the face and diagnosed with mandibular parasymphyseal fractures. Their age ranged from 18-50 with mean age 25 years old. b) Exclusion criteria: patients with any comminuted fractures, associated pathology or bone disease and uncontrolled debilitating systemic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The Results of the present study is in accordance with Zakaullah S et al (24) . Helmy A et al (25) . As they reported that there was no segment mobility, nonunion or malunion.…”
Section: Discussionmentioning
confidence: 99%
“…The Results of the present study is in accordance with Zakaullah S et al (24) . Helmy A et al (25) . As they reported that there was no segment mobility, nonunion or malunion.…”
Section: Discussionmentioning
confidence: 99%